Let's take it outside: Seeking alternative targets for expressing dissent at work when voice is suppressed. (November 2022) - Akkerman, Agnes; Sluiter, Roderick; Manevska, Katerina
This study examines what workers do when their supervisor is not responsive to their voice. Based on mobilization theory and theories on organizational dissent, the authors hypothesize alternatives for workers expressing discontent when their initial complaints are ignored or punished by their supervisor under various co-worker support conditions. The hypotheses are tested using a large- N dataset while applying a vignette design. The findings show that workers are less likely to (repeat) voice within the organization and more likely to seek help outside the organization when a supervisor threatens to punish future voice endeavours. Co-workers' supportive and participative responses to voice increase the likelihood that workers keep their voice within the organization and have mixed effects on the likelihood that workers seek support elsewhere.